Gut-lung Axis mediates asthma pathogenesis: Roles of dietary patterns and their impact on the gut microbiota - Yanbo Liu; Ying Zhou; Haoyue Zhang; Kaixuan Zhao; Dong Yang (Experimental and Molecular Pathology)
The gut-lung axis, a vital signaling network linking the gastrointestinal and pulmonary systems, regulates immune responses and the progression of respiratory diseases. Nutritional components can modulate the gut microbiome and regulate the synthesis of critical intestinal microbial metabolites, which are essential for maintaining immune homeostasis and supporting respiratory health. Conversely, poor dietary habits exacerbate asthma and other respiratory conditions through the modulation of systemic inflammation and immune responses. Dietary interventions, such as the Mediterranean diet, are reported to restore microbial balance and improve respiratory health by increasing the production of anti-inflammatory metabolites, potentiating immune responses, and preserving epithelial barrier integrity. In contrast, Western dietary patterns, which are characterized by high fat and low fiber intake, disrupt microbial diversity, resulting in increased levels of pro-inflammatory metabolites that aggravate airway inflammation and asthma severity. This review aimed to elucidate the mechanisms underlying the regulatory effects of gut microbes and their metabolites on asthma. Additionally, previous findings related to the gut-lung axis have been summarized, providing insights into potential therapeutic strategies for asthma management.